The zinc receptor, ZnR/GPR39, modulates taste sensitivity by regulating ion secretion in mouse salivary gland - Moran Melamed; Hila Asraf; Noa Livne; Milos Bogdanovic; Anil Shendge; Gilad Shamir; Maayan Mero; Omer Adir; Avi Schroeder; Israel Sekler; Michal Hershfinkel (iScience)
Summary: Reduced saliva secretion, dry mouth, and loss of taste are debilitating symptoms associated with zinc deficiency. A mechanism for zinc regulation of these processes is lacking. Here, we identified the Zn2+ sensing receptor ZnR/GPR39 as a mediator of ion transport in salivary gland epithelium. By monitoring transport of NH4+, a surrogate for K+, we revealed that Zn2+ upregulates the Na+/K+ ATPase pump activity in parotid and submandibular salivary gland epithelium from wildtype (WT), but not from ZnR/GPR39 knockout (KO), mice. Since Na+/K+ ATPase activity is crucial for solute transport, we compared saliva composition in WT and ZnR/GPR39 KO mice and found impaired ionic concentration and reduced saliva secretion in ZnR/GPR39 KO mice. Moreover, mice deficient in ZnR/GPR39 exhibited decreased sensitivity to appetitive Na+ concentrations. Altogether, we demonstrate that salivary ZnR/GPR39 activity controls saliva ion composition and secretion, and provides a target for therapeutic approaches for dry mouth and taste disorders.